Phytochemical and antimicrobial studies of Phyllanthus wightianus leaf extract - Joseph M; Charles A; Ramani V (International Journal of Phytomedicine, 2012)
The genus Phyllanthus contains highly valued medicinal plants which produce a variety of secondary metabolites. The present paper was designed to carry out preliminary phytochemical screening and antimicrobial activity of leaves of Phyllanthus wightianus. The dried leaves of the plant were subjected to phytochemical analysis by using of systematic extraction method. The ethanolic extract of leaves of P. wightianus was screened for antimicrobial activity on 20 types of pathogenic bacteria. The investigation reveals that the leaves of P. wightianus contain phytoconstituents-alkaloids, terpenoids, flavanoids, tannins and carbohydrates. The ethanolic extract of the plant showed good antimicrobial resistance.